Comportamiento agronómico y valor nutricional de tres variedades de pastos pennisetum para corte en la zona de Pichilingue Provincia de Los Ríos. - Arias Lara, José Luis (2012)
The need to increase the production of the land available for farming, forcing producers to turn to alternatives that provide volume but turn print quality for the production, so they must implement pasture managed under a cut and carry , in order to meet the daily needs of the herds. One of the most widely used varieties of grass is the Pennise tum is characterized by good quality biomass production nu ¬ tricional acceptable. The objective of this research was to evaluate the agronomic performance and nutrition of three species of grass cutting at different maturity status agronomic data and nutrient values were taken at 40.50 and 60 days of 811 Cuba Iniap Pennisetum CT115 and king grass purple; This research was conducted in the fields of experimental station of the National Institute Pichilingue Tropical Agricultural Research (INIAP) located on the road Quevedo Km 5 the Canton Junction Mocache parish Quevedo the province of Los Ríos.